The Impact of Marketing Transparency on Purchase Intentions Through Perceptions of Fairness and Brand Image in Indonesia - Haryanti, Titi; Arini, Rani Eka (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the effect of marketing transparency on purchase intention through the mediating roles of perceived fairness and brand image in the Indonesian consumer market. As transparency becomes increasingly important in contemporary marketing practices, understanding its psychological and behavioral implications is essential for firms operating in competitive and information-rich environments. This research adopts a quantitative approach by collecting data from 150 Indonesian consumers using a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. The results reveal that marketing transparency has a significant positive effect on perceived fairness and brand image. Furthermore, perceived fairness and brand image both significantly influence purchase intention, with brand image showing a stronger effect. The mediation analysis confirms that perceived fairness and brand image partially mediate the relationship between marketing transparency and purchase intention, indicating that transparency primarily affects purchase intention indirectly by shaping consumers’ fairness perceptions and brand evaluations. These findings contribute to the marketing literature by clarifying the underlying mechanisms through which marketing transparency influences consumer behavior in an emerging market context. Practically, the study highlights the strategic importance of transparent marketing communication in fostering fair perceptions, strengthening brand image, and enhancing consumers’ purchase intentions in Indonesia.